Reducing institutional disorder: using the inmate risk assessment for segregation placement to triage treatment services at the front end of prison sentences - Labrecque, Ryan M. (Crime & delinquency, 2019)
Most correctional scholars and policy makers agree that prison authorities should use restrictive housing less, yet few studies exist to provide guidance on how to do so while also ensuring institutional order. This study advances the idea that proactively providing rehabilitative programming to inmates at the front end of prison sentences will help reduce institutional disorder. In so doing, we create and validate a risk assessment instrument to predict inmate likelihood for placement in restrictive housing during one’s commitment. The findings of this study support the predictive validity of the tool. We argue that authorities can use this assessment to make more informed and targeted programming decisions during the intake process that will help reduce institutional misconduct and the need for restrictive housing.